On the belief universal gravitation (BUG) - Mi, Xiangjun; Kang, Bingyi (Computers & industrial engineering, 2020)
•A new concept BUG is proposed in the D-S evidence theory.•BUG provides a new perspective for information fusion in evidence theory.•BUG formula is based on evidence distance, EQC algorithm, etc. In this paper, we proposed a notion of belief universal gravitation (BUG) in the Dempster-Shafer (D-S) evidence theory, of which the notion of mass of a belief function is newly addressed using evidence quality coding (EQC) method. The proposed BUG aims to discuss the process of information fusion from the perspective of Newton’s mechanics, which may provide us a new insight to address the issues of D-S evidence theory. A key issue in D-S evidence theory, i.e., conflict management, is solved better than previous methods using the proposed BUG. An application in fault diagnosis is used to illustrate the effectiveness of the proposed BUG. Some further work is also summarized to present the potentials of the proposed BUG.